KINERJA OJEK ONLINE DAN KONVENSIONAL DI KOTA KENDARI - Soeparyanto, Try Sugiyarto; Royani, Waode; Arsyad, La Ode Muhammad Nurrakhmad; Statiswaty (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
This study aims to measure the performance of two-wheeled public transportation, online and conventional motorcycle taxis. Snowballing technology penetrates the transportation sector and provides convenience and flexibility at users' fingertips. Users are faced with a choice of online and conventional transportation that still survives today. Using the perception assessment approach, the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods use a Likert rating scale for users who use online motorcycle taxis and conventional motorcycle taxis. There are five variables: Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results show that CSI for online motorcycle taxis has a value of Very Satisfied to Satisfied. In contrast, for conventional motorcycle taxis, there is a variable with a value of Very Dissatisfied, namely Reliability, and Assurance has a value of Fairly Satisfied. Other than that, it's worth Very Satisfying. The IPA method describes these variables into 56 attributes, detailed in 11 attributes in Quadrant I, namely the Top Priority category, and 17 attributes in Quadrant II, namely Maintain Achievement. The others are included in Quadrants III and IV with low importance. Abstrak Penelitian ini bertujuan untuk mengukur kinerja angkutan umum roda dua, ojek online dan konvensional. Penggunaan teknologi yang berkembang pesat merambah hingga ke sektor transportasi dan memberikan kemudahan serta fleksibilitas di ujung jari pengguna. Pengguna dihadapkan dengan pilihan akan transportasi online maupun konvensional yang masih bertahan hingga kini. Dengan pendekatan penilaian persepsi metode Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) menggunakan skala penilaian Likert terhadap masyarakat pengguna yang menggunakan ojek online dan ojek konvensional. Terdapat 5 variabel yaitu: Tangible, Reliability, Responsiveness, Assurance, dan Empathy. Hasil menunjukkan bahwa CSI untuk ojek online bernilai Sangat Puas hingga Puas, sedangkan untuk ojek konvensional terdapat variabel yang bernilai Sangat Tidak Puas yaitu Reliability, dan Assurance bernilai Cukup Puas. Selain itu bernilai Sangat Puas. Metode IPA menjabarkan variabel tersebut ke dalam 56 atribut, yang terinci pada 11 atribut dalam Kuadran I yaitu kategori Prioritas Utama, 17 atribut dalam Kuadran II yaitu Pertahankan Prestasi. Adapun lainnya masuk dalam Kuadran III dan IV dengan kepentingan rendah.